Correlation Between Parenting With Social Intreraction in Autism Children In Pontianak City - Nurmanila, Nurmanila (Universitas Tanjungpura, 2020)
Background: Autism is a severe developmental disorder that appears in beginning in the first three years of their life and continuing throughout their life if left untreated. WHO in 2018 reported that 1 in 160 children have autism spectrum disorders. In 2019, a total of 91 children were diagnosed with autism spectrum disorders in Pontianak city. This data was obtained based on the report of 5 handling children places with autism spectrum disorders in Pontianak city, West Kalimantan. Autism spectrum disorder starts from childhood to last through adolescence and adulthood. Parenting is one of the factors that has a major influence on the formation of children character. Purpose: To find out whether there is a correlation between parenting parent with sosial interaction in autism children in Pontianak City. Method: Quantitative research using Cross Sectional design with correlative hypotheses. This study was conducted to 74 respondents of parents (mothers). The instrument used Parenting Styles and Dimensions Questionnaire-Short Form sheet and the Checklist for Evaluation of Autism Therapy Questionnaire. Test used in this research was the Contingency Coefficient test with decision making using V Cramer's value. Result: The results of this research obtained a democratic parenting (41.9%) which results in good social interaction (24.3%). P value of 0,000 and 95% value or ik 3,260 (1,246-8,533). Conclusion: There is a correlation between parenting and social interaction in autism children in Pontianak City.